Perceived menu variety, taste, and price fairness as predictors of consumer purchase decisions at Shizuka Burger Tower Resto, Kisaran - Lukman Nul Hakin Marpaung; Surya Bakti (Priviet Social Sciences Journal, 2026)
The rapid expansion of Indonesia’s fast-food and casual-dining sectors has intensified competition among local burger outlets. Therefore, it is important to identify the marketing mix attributes that are most closely associated with consumer buying behaviors. This study examined the associations and predictive relationships between perceived menu variety, taste, perceived price fairness/value-for-money, and customers’ purchase decisions at Shizuka Burger Tower Resto in Kisaran, Indonesia. A quantitative cross-sectional associative survey design was employed. Primary data were collected through a five-point Likert questionnaire administered to 96 customers selected by accidental (non-probability) sampling and analyzed using multiple linear regression in IBM SPSS Statistics 22 after validity, reliability, classical assumption, and common method bias checks. The three predictors jointly explained a substantial 82.4% of the variance in purchase decisions, F(3, 92) = 143.582, p < .001. However, the partial pattern was uneven: perceived price fairness/value-for-money showed the strongest positive predictive association (β = .642, p < .001), taste also showed a significant positive predictive association (β = .325, p < .001), whereas menu variety was essentially unrelated to purchase decision (β = −.005, t = −0.058, p = .954). Harman’s single-factor test showed that the first unrotated factor accounted for 55.83% of the total item variance, indicating that common method variance may be present and that the high R² should be interpreted cautiously. Because the design was cross-sectional, non-experimental, and based on same-source questionnaire data, these findings should be interpreted as perceived and predictive relationships rather than definitive causal effects of the variables.